The role of RIPK3‐regulated cell death pathways and necroptosis in the pathogenesis of cardiac ischaemia‐reperfusion injury. (7th August 2020) - Ying, Luo; Benjanuwattra, Juthipong; Chattipakorn, Siriporn C.; Chattipakorn, Nipon
Abstract: Despite advancements in management of acute myocardial infarction, this disease remains one of the leading causes of death. Timely reestablishment of epicardial coronary blood flow is the cornerstone of therapy; however, substantial amount of damage can occur as a consequence of cardiac ischaemia/reperfusion (I/R) injury. It has been previously proposed that the pathway leading to major cell death, apoptosis, is responsible for cardiac I/R injury. Nevertheless, there is compelling evidence to suggest that necroptosis, a programmed necrosis, contributes remarkably to both myocardial injury and microcirculatory dysfunction following cardiac I/R injury. Receptor‐interacting protein kinase 1 (RIPK1), RIPK3, and mixed‐lineage kinase domain‐like pseudokinase (MLKL) are shown as the major mediators of necroptosis. In addition to the traditional perception that RIPK1/RIPK3/MLKL‐dependent plasma membrane rupture is fundamental to this process, several RIPK3‐related pathways such as endoplasmic reticulum stress and mitochondrial fragmentation have also been implicated in cardiac I/R injury. In this review, reports from both in vitro and in vivo studies regarding the roles of necroptosis and RIPK3‐regulated necrosis in cardiac I/R injury have been collectively summarized and discussed. Furthermore, reports on potential interventions targeting these processes to attenuate cardiac I/R insults to the heart have been presented in this review. Future investigations adding to the knowledge obtained from these previous studies are needed in the pursuit of discovering the most effective pharmacological agent to improve cardiac I/R outcomes.